Molecular changes, histopathology, and ultrasonic vocalization acoustic profiles of systemically dehydrated rats - Brooke Rodgers; Naila Cannes do Nascimento; Abigail Cox; Taylor W. Bailey; M. Preeti Sivasankar; Allison J. Schaser (PLoS ONE, 2025)
Systemic hydration is known to promote optimal functioning of bodily systems—including the vocal folds. The impact of systemic dehydration on the biology of the vocal folds and the downstream effects of dehydration on voice output are not well understood. An in vivo rat model of systemic dehydration was employed to investigate vocal fold gene expression, histological changes, and acoustic changes in vocalization. Ultrasonic vocalizations (USVs) were recorded every day for 5 days (baseline), in male and female Long-Evans rats (N = 36, ages: 3–4 months) using an anticipatory reward paradigm. Next, rats were dehydrated (N = 18) using a published water-restriction model for 5 days or euhydrated (N = 18) and provided ad libitum access to water for 5 days. USVs were recorded daily during the dehydration/euhydration period. The USV variables were averaged at baseline and following dehydration/euhydration for individual animals, and the difference between these time periods was used for statistical analysis. USV analysis included total USV count, complexity ratio, duration (s), frequency range (kHz), and maximum intensity (dB). At the end of dehydration/euhydration, animals were euthanized, and kidney and vocal fold tissue samples were dissected and processed for histology and gene expression analysis. Compared to euhydrated rats, dehydrated male and female rats had significantly up-regulated gene expression of kidney renin (male p = 0.047; female p = 0.018), indicating physiologic dehydration. There were no statistically significant differences in the USV acoustic profile or histopathology between the two groups. Differential expression (p < 0.05) of several genes related to extracellular matrix remodeling, inflammatory responses, and water ion transport in the vocal folds was present. Our results indicate that mild systemic dehydration impacts gene expression in the vocal fold mucosa; however, these gene expression changes are not evident in the acoustic profile of vocalizations.